Achieving Balanced Crystallization Kinetics of Donor and Acceptor by Sequential‐Blade Coated Double Bulk Heterojunction Organic Solar Cells. Issue 28 (11th June 2020) - Wang, Yilin; Wang, Xiaohui; Lin, Baojun; Bi, Zhaozhao; Zhou, Xiaobo; Naveed, Hafiz Bilal; Zhou, Ke; Yan, Hongping; Tang, Zheng; Ma, Wei
Abstract: Sequential deposition has great potential to achieve high performance in organic solar cells due to the resulting well‐controlled vertical phase separation. In this work, double bulk heterojunction organic solar cells are fabricated by sequential‐blade cast in ambient conditions. Probed by the in situ grazing incidence X‐ray diffraction and in situ UV–vis absorption measurements, the seq‐blade system exhibits a different tendency from each of the binary films during the film formation process. Due to the extensive aggregation of FOIC, the binary PBDB‐T:FOIC film displays a strong and large phase separation, resulting in low current density ( J sc ) and unsatisfactory power conversion efficiency. In the seq‐blade cast system, the bottom layer PBDB‐T:IT‐M produces many crystal nuclei for the top layer PBDB‐T:FOIC, so the PBDB‐T molecules are able to crystallize easily and quickly. Balanced crystallization kinetics between polymer and small molecule and an ideal percolation network in the film are observed. In addition, the balanced crystallization kinetics are favorable toward realizing lower recombination loss through charge transport processes. Abstract : A successful double bulk heterojunction is fabricated with a blade coating method, which sheds light on innovative approaches to rationally realize balanced crystallization kinetics for donors and acceptors and further improve the photovoltaic efficiency of organic solar cells.